(untitled) (Biological Sciences - PJSIR, 1998)
Acid activation of washed D.G. Khan fuller’s earth has been investigated with regard to parameters such as concentration of acid, percentage of slurry solids, duration 01’ heating and temperature. It has been found that the fuller’s earth may be activated to a J11RximUIllpossible degree with varying sets or these parameters. The maximum activation achieved with (HC I)6N acidulation for 2 hours activation time is suitable 1’01’ producing a commercially acceptable product.